The transcriptional activator GaaR of Aspergillus niger is required for release and utilization of d‐galacturonic acid from pectin - Alazi, Ebru; Niu, Jing; Kowalczyk, Joanna E.; Peng, Mao; Aguilar Pontes, Maria Victoria; Kan, Jan A. L.; Visser, Jaap; Vries, Ronald P.; Ram, Arthur F. J. (FEBS letters, 2016)
We identified the d‐galacturonic acid (GA)‐responsive transcriptional activator GaaR of the saprotrophic fungus, Aspergillus niger, which was found to be essential for growth on GA and polygalacturonic acid (PGA). Growth of the ΔgaaR strain was reduced on complex pectins. Genome‐wide expression analysis showed that GaaR is required for the expression of genes necessary to release GA from PGA and more complex pectins, to transport GA into the cell, and to induce the GA catabolic pathway. Residual growth of ΔgaaR on complex pectins is likely due to the expression of pectinases acting on rhamnogalacturonan and subsequent metabolism of the monosaccharides other than GA.